2017
DOI: 10.1093/mnrasl/slx166
|View full text |Cite
|
Sign up to set email alerts
|

A progenitor model of SN 1987A based on the slow-merger scenario

Abstract: Even after elaborate investigations for 30 years, we still do not know well how the progenitor of SN 1987A has evolved. To explain unusual red-to-blue evolution, previous studies suggest that in a red giant stage either the increase of surface He abundance or the envelope mass was necessary. It is usually supposed that the He enhancement is caused by the rotational mixing, and the mass increase is by a binary merger. Thus, we have investigated these scenarios thoroughly. The obtained findings are that rotating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…As discussed in Sections 4.2 and 4.3, among the investigated models in this paper, there is no explosion model with the BSG model n16.3 that satisfies the two observational constraints on the mass of high velocity 56 Ni simultaneously. On the other hand, with the BSG model b18.3 (binary merger model: Urushibata et al 2018) and two other RSG models s18.0 and s19.8 (Woosley et al 2002;Sukhbold et al 2016), we found several explosion models that satisfy the constraints. Thus, important questions are which properties of the pre-supernova models are essential to the matter mixing and why the properties have an advantage in the matter mixing.…”
Section: Key Properties Of the Progenitor Models And Their Impact Onmentioning
confidence: 73%
See 4 more Smart Citations
“…As discussed in Sections 4.2 and 4.3, among the investigated models in this paper, there is no explosion model with the BSG model n16.3 that satisfies the two observational constraints on the mass of high velocity 56 Ni simultaneously. On the other hand, with the BSG model b18.3 (binary merger model: Urushibata et al 2018) and two other RSG models s18.0 and s19.8 (Woosley et al 2002;Sukhbold et al 2016), we found several explosion models that satisfy the constraints. Thus, important questions are which properties of the pre-supernova models are essential to the matter mixing and why the properties have an advantage in the matter mixing.…”
Section: Key Properties Of the Progenitor Models And Their Impact Onmentioning
confidence: 73%
“…Thus, the BSG progenitor models based on the single star evolution have both pros and cons. On the other hand, the binary merger model b18.3 (Urushibata et al 2018), which satisfies all observational constraints including the luminosity of Sk −69 • 202, has a smaller helium core mass (q value) than those of models based on the single star evolution that satisfy the luminosity of Sk −69 • 202, which may reflect the nature of merging processes, the penetration of the secondary into the envelope of the primary and the dredge up of the primary's core material into the envelope. Actually, the recent other binary merger models (Menon & Heger 2017) that satisfy the observational constraints all have a small helium core mass of ∼ 3-4 M (q ∼ 0.1-0.2) (see Table 4 in Menon & Heger 2017).…”
Section: Key Properties Of the Progenitor Models And Their Impact Onmentioning
confidence: 99%
See 3 more Smart Citations